2016
DOI: 10.7863/ultra.15.07073
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Uterine Subseptations: What Length Should Warrant Hysteroscopic Resection?

Abstract: The relevance of subseptations shorter than 10 mm is currently undetermined and underestimated. Our data indicate a new subseptation cutoff length with postoperative remodeling and statistical relevance similar to longer subseptations. We propose a revision of the recommendations for surgical correction to include the objectively obtained subseptation length greater than or equal to 5.9 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…This work reinforces the idea of uterine remodeling after hysteroscopic metroplasty [25,26], due to the intrinsic histological characteristics of the septum, and the ability of the myometrium to modify the shape and thickness of the uterine walls not only in physiological conditions such as pregnancy, but also iatrogenic, such as surgery.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This work reinforces the idea of uterine remodeling after hysteroscopic metroplasty [25,26], due to the intrinsic histological characteristics of the septum, and the ability of the myometrium to modify the shape and thickness of the uterine walls not only in physiological conditions such as pregnancy, but also iatrogenic, such as surgery.…”
Section: Discussionsupporting
confidence: 82%
“…The 3D-transvaginal sonography (3D-TVS) is currently the most widely used method for the initial study of the uterine morphology and can also be performed to study/evaluate the outcomes of hysteroscopic metroplasty [23,24]. To date, few studies has shown the modifications of the profile of uterine cavity after hysteroscopic metroplasty [25,26]. Instead, to our knowledge, this is the first work that analyzes the uterine fundal morphology before and after hysteroscopic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 70% of in utero DES-exposed women had uterine abnormalities. 11 The most common anomalies were T configuration and hypoplasia of the uterus. The other associated abnormalities were strictions, adhesions, and rudimentary horn.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,10 In addition, a recent prospective controlled cohort trial hypothesized that infertility and adverse pregnancy outcomes may be as a result of a wider and misshapen cavity, the length of the uterine septa, and a decreased endometrial surface. 11 On the contrary, a T-shaped uterus (class U1a) is a rare uterine malformation which has been reported frequently in women exposed in utero diethylstilbestrol (DES). 12 Although the pathogenesis and the etiology still remains unknown, in some cases it may be due to Asherman syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation